Relationship between occlusal force and endothelial function in community‐dwelling elderly women: A pilot study. Issue 5 (22nd July 2022) - Kato, Kanna; Matsuda, Naoko; Takahata, Miki; Koseki, Chika; Yamaki, Michiyasu; Sato, Toshiaki
Abstract: Objective: In this study, age, endothelial function as flow‐mediated dilation (FMD), occlusal force, grip strength, and advanced glycation end products (AGEs) were obtained. AGEs were measured as indicators of aging, while grip strength was measured as an indicator of muscle strength. This study aimed to explain the relationship between occlusal force and endothelial function and determine whether occlusal force can be a new indicator in community preventative care projects. Materials and Methods: In 38 community‐dwelling women (age, 76.7 ± 5.7 years), the occlusal force and grip strength were measured, the endothelial function was evaluated by FMD, and AGEs were obtained. The relationship between occlusal force, measurement items, and factors were investigated independently related to endothelial function. Results: There were significant correlations between occlusal force and grip strength ( r  = .54, p  < .01). The degree of FMD was significantly associated with occlusal force ( r  = .60, p  < .01) and grip strength ( r  = .35, p  < .05) or increase in AGEs ( r  = −.37, p  < .05). Multiple regression analysis revealed that occlusal force was significantly associated with the degree of FMD ( p  < .01). Conclusion: Occlusal force can be an important indicator of endothelial function in the community‐dwelling elderly. This study may help understand the general health of the elderly in communities.